2021
DOI: 10.1039/d1ma00118c
|View full text |Cite
|
Sign up to set email alerts
|

Integrating superconducting van der Waals materials on paper substrates

Abstract: Paper has the potential to dramatically reduce the cost of electronic components. In fact, paper is 10 000 times cheaper than crystalline silicon, motivating the research to integrate electronic materials...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…18,24,25 To understand the origin of the resistance distribution and model the transport through the disordered WS 2 films we propose a random resistor network (RRN) model, 26,27 which we used in a previous article to model the superconducting transport transition in a disordered film of NbSe 2 on paper. 12 Fig. 3a shows a schematic of the physical devices and a zoomed-in sketch of the WS 2 film composed of interconnected WS 2 platelets.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…18,24,25 To understand the origin of the resistance distribution and model the transport through the disordered WS 2 films we propose a random resistor network (RRN) model, 26,27 which we used in a previous article to model the superconducting transport transition in a disordered film of NbSe 2 on paper. 12 Fig. 3a shows a schematic of the physical devices and a zoomed-in sketch of the WS 2 film composed of interconnected WS 2 platelets.…”
Section: Resultsmentioning
confidence: 99%
“…10,11 This method, which has been demonstrated first with graphite (from pencils), has been extended only recently to other van der Waals materials, such as semiconducting MoS 2 or WS 2 or superconducting NbSe 2 . 12,13 Achieving highly conductive films using ink suspensions containing vdW materials is challenging, due to the presence of solvent-related adsorbates on the deposited vdW materials that Riccardo Frisenda RF earned his PhD title from TU Delft in 2016 under the supervision of Prof. van der Zant with a thesis about electrical transport through single-molecules contacted by movable nano-electrodes. After his PhD, RF moved as a postdoc to the laboratory of Dr.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the WS 2 photoactive channel can be made as narrow as ~300 μm despite utilizing this manual "abrading/drawing " method. A recent combined scanning electron microscopy and atomic force microscopy study of abrasion-induced deposited WS 2 on polycarbonate showed that the abrasion forces experienced during the rubbing process lead to a reduction of the thickness of the WS 2 deposited flakes, from ~100−200 nm in the as-received powder to ~20−80 nm for the abraded WS 2 films 35 . We refer readers to our previous work for further characterizations on morphology and structure 46 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we demonstrated the integration of different van der Waals materials on standard printer/copy paper (untreated) through direct abrasion of powders of van der Waals materials against the rough surface of paper. [14][15][16][17][18] This deposition process is similar to drawing/writing with a pencil on paper: the friction force generated when a van der Waals material is rubbed against paper cleaves the crystals leading to a network of interconnected platelets.…”
mentioning
confidence: 99%